1993
DOI: 10.1056/nejm199304083281402
|View full text |Cite
|
Sign up to set email alerts
|

A Defective Visual Pathway in Children with Reading Disability

Abstract: The pattern of results suggests that the response of the magnicellular visual pathway is slowed in reading-disabled children, who do not, however, have a general slowing of the visual response. The possibility that there is a cause-and-effect relation between these findings and reading disability will require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(91 citation statements)
references
References 26 publications
5
83
0
3
Order By: Relevance
“…However, the transient system theory has some empirical support (Breitmeyer, 1989;Badcock & Lovegrove, 1981;Lehmkuhle, Garzia, Turner, Hash, & Baro, 1993;Lovegrove et al, 1986;Lovegrove, Garzia, & Nicholson, 1990;Martin & Lovegrove, 1984), as does the motion perception theory (Eden et al, 1996). Thus, both warrant further comment.…”
Section: Visual Deficitsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the transient system theory has some empirical support (Breitmeyer, 1989;Badcock & Lovegrove, 1981;Lehmkuhle, Garzia, Turner, Hash, & Baro, 1993;Lovegrove et al, 1986;Lovegrove, Garzia, & Nicholson, 1990;Martin & Lovegrove, 1984), as does the motion perception theory (Eden et al, 1996). Thus, both warrant further comment.…”
Section: Visual Deficitsmentioning
confidence: 94%
“…Yet, it might be a correlate of the disorder, and perhaps even a biological marker. This possibility is given some Specific reading disability (dyslexia) support by anatomical and electrophysiological studies demonstrating structural and functional anomalies in the magnocellular pathways of a small number of those with dyslexia studied (Lehmkuhle et al, 1993;Livingstone, Rosen, Drislane, & Galaburda, 1991). However, a recent review of the literature by Skottun and Parke (1999) presented evidence from several studies of saccadic suppression that strongly suggests that it is the magnocellular system that is suppressed during saccadic movements of the eyes, not the parvocellular system.…”
Section: Visual Deficitsmentioning
confidence: 99%
“…Specific reading disability in a small subset of patients with dyslexia has been attributed to a deficit in the magnocellular visual system. [183][184][185][186][187] In 1983, Breitmeyer 183 proposed that reading disability is an expression of the disruptive effects of a temporal processing deficit in the magnocellular system. Stein and Walsh 184,187 suggested that this deficit in the inhibitory function of the magnocellular system produces a visual trace of abnormal longevity that creates masking effects along with visual acuity problems when reading connected text.…”
Section: Magnocellular Deficit Theorymentioning
confidence: 99%
“…Also in opposition to Livingstone et al, May et al 189 found that the latency periods were shortened under low spatial frequency conditions. In 1993, Lehmkuhle et al 185 noted the lack of change in the latency of the visual evoked potential in reading-disabled children compared with the increased latency noted in children without a reading disability by using low spatial frequency target and high-frequency flicker fields. Their conclusion was that it is possible that a defect in the magnocellular pathway creates a timing disorder that precludes rapid and smooth integration of detailed visual information necessary for efficient reading.…”
Section: Magnocellular Deficit Theorymentioning
confidence: 99%
See 1 more Smart Citation